Distribution of the parasite Fasciola gigantica in the intermediate host in Al-NajafAl-Ashraf Governorate - Gzi, muna (University of Thi-Qar Journal of Science, 2019)
This study included the detection of the Prevalence rate of Fasciola gigantica parasite in intermediate host in Najaf governorate from July 2009 to June 2010. The intermediate host (Lymneae auricularia) collected from three regions (Bahar Al -Najaf, Kufa and Manadhera) were found to be most susceptible to be infected by this parasite. The prevalence rate recoded in this study was 5.08 % in Manadhera, 2.45 % in Kufa and 0.92 % in Bahar Al -Najaf.